2012
DOI: 10.1002/dvdy.23865
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the hypoxic response: Another job for miRNAs?

Abstract: Living organisms are constantly exposed to environmental and genetic perturbations. Biological robustness enables these organisms to maintain their functional stability in the presence of external or internal changes. It has been proposed that microRNAs (miRNAs), small non-coding regulatory RNAs, contribute to robustness of gene regulatory networks. The hypoxic response is a major and well-characterized example of a cellular and systemic response to environmental stress that needs to be robust. miRNAs regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
(104 reference statements)
1
2
0
Order By: Relevance
“…In this way, miR‐155 promotes the resolution of hypoxia inducible factor‐1α activity in hypoxia . A similar phenomenon was most recently described for miR‐210 , which controls host responses to hypoxia by promoting the induction of autophagic pathways but also by targeting hypoxia‐inducible factor‐1α, thereby limiting the duration of the hypoxic reaction .…”
Section: Mirnas In Periodontitis and Periodontitis‐related Mechanismssupporting
confidence: 64%
“…In this way, miR‐155 promotes the resolution of hypoxia inducible factor‐1α activity in hypoxia . A similar phenomenon was most recently described for miR‐210 , which controls host responses to hypoxia by promoting the induction of autophagic pathways but also by targeting hypoxia‐inducible factor‐1α, thereby limiting the duration of the hypoxic reaction .…”
Section: Mirnas In Periodontitis and Periodontitis‐related Mechanismssupporting
confidence: 64%
“…Of critical importance, epigenetic-mediated regulations play a central role in the cell's response pathways that are crucial for adaptation to hypoxia (593,717,1039). Epigeneticrelated mechanisms of DNA methylation, histone modifications, and microRNAs have all been shown to be important in maternal, placental, and fetal responses to hypoxia in gestation (156,183,212,305,616,691,754,1129). Recent studies in several animal models including gestational hypoxia have shown significant changes in gene ex-Table 3.…”
Section: Hypoxia and Epigenetic Programmingmentioning
confidence: 99%
“…A prototypical example is miR-210, which is HIF inducible and was initially identified in cancer cells (92). More recently, miR-210 was shown to function as a negative regulator of HIF-1␣ in T cells (161), illustrating that hypoxia-and also non-hypoxia-regulated miRs operate in complex feedback loops that can amplify or suppress HIF-controlled pathways (31) and thus have the potential to modulate IPC. For example, miR-199a is suppressed under hypoxic conditions and modulates HIF-1-induced preconditioning in cardiomyocytes by directly targeting HIF-1␣ and SIRT1-induced suppression of PHD2 (131).…”
Section: F827mentioning
confidence: 99%